Consumer Behaviour Towards Grocery Online Shopping During Pandemic: Case Study in Sayurbox - Desyra Sukma Dewanthi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
The use of online groceries is increasing during the pandemic. In America, the increase reached 52% with 20% of shoppers being new users. Based on the survey conducted, it has shown that the Sayurbox is one of the online shops favored by the public to shop for vegetables and other necessities. As many as 24% of the sample used Sayurbox and Happyfresh, 19% used Shopee, 14% used Go-Mart, 9% chose Tokopedia, and 5% used Tanihub and Hypermart. During the pandemic, the trend of cooking the own food began to increase. This has resulted in increased demand for staple food. People are turning to buying healthier and more sustainable food. This research used a qualitative method. It is used to examine the condition of the object naturally with a combined data collection technique. According to this approach, the researcher begins with specific observations to produce a general theory and conclusions drawn from the research. The reason for using an inductive approach is that it considers the context in which the research effort is active, while it is also most appropriate for small samples that produce qualitative data. Data collected by observation, in-depth interviews, and literature study. The object of this research is that people often use online grocery shopping during this pandemic. Samples that has been taken as respondents are those aged 21 to 35 years. Demographic segmentation of Sayurbox are those who is in age of 18 until 50 years. They are a technology literate society with access to the internet. This community is a society that has the economic capacity to make purchases so that the closest people to this segment are workers who have not been or are already married. Potential area are Jakarta, Tangerang, Bekasi, and Depok. Sayurbox refers to the market segment of people who choose an instant lifestyle. Their life is full of busy so, they have no time to shop. They will more comfortable and easier to use services such as Sayurbox to provide food and basic necessities. This behavioral segment is aimed at people who have a tendency to be willing to pay postage and services for someone who has helped them get the goods they need. The motive of someone making a purchase at Sayurbox was most influenced by pandemic conditions. This platform provides a variety of vegetables, fruit, side dishes, beverage ingredients, dairy, package menus, and others to full household necessities in food. Some people use this platform to reduce the risk of being infected with Covid-19. In addition, consumers are also given the convenience and several discounts hitch make them even more diligent in using this platform. Those who use the services from Sayurbox are 21 - 35 years old consumers with a variety of professions. Based on the sample interviewed, it can be concluded that students, workers, and housewives use this platform to full their needs.